Pengaruh Anemia terhadap Stomatitis Aftosa Rekuren: Laporan Kasus - Cholifatul Laili Ziamona; Sartari Entin Yuletnawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Recurrent aphthous stomatitis (RAS) is a common inflammatory condition of the oral mucosa characterized by round or oval ulcers with well-defined reddish borders and a shallow base covered by a grayish or yellowish fibrinous pseudomembrane. RAS is generally classified into three clinical types—minor, major, and herpetiform based on the size, number, and duration of the lesions. Several factors contribute to its occurrence, including bacterial infections such as Streptococcus sanguis, immune system dysfunctions, and nutritional deficiencies involving iron, vitamin B12, and folic acid. Other potential triggers include local trauma, hormonal or endocrine imbalances, psychological stress, and allergic reactions. Among these, anemia due to deficiencies in iron, folate, or vitamin B12 is considered an important etiopathogenic factor, although its exact role has not been fully clarified. The management of RAS primarily focuses on symptom relief, promoting faster ulcer healing, and preventing recurrence through both topical and systemic approaches. Effective treatment often includes improving nutritional intake, maintaining oral hygiene, and addressing underlying systemic or psychological conditions. Understanding the multifactorial causes of RAS is crucial in developing comprehensive strategies for prevention and long-term management of this recurrent oral lesion.